Isotretinoin update. Issue 6 (22nd December 2021) - Marson, Justin W.; Baldwin, Hilary E.
Abstract: Background: Acne is a common, chronic inflammatory condition seen in nearly all teenagers and many adult females, with a global lifetime prevalence between 70‐85%. While a majority of individuals with acne can be appropriately managed with a combination of topical therapies, oral antibiotics, and/or oral anti‐androgens, 10‐20% of individuals will have acne severe enough to warrant isotretinoin. When necessary, isotretinoin is highly effective and the only drug to offer the likelihood of a durable response. Aims: To review the literature regarding known adverse effects of isotretinoin therapy and nuances during and post‐isotretinoin therapy important to patient care. Materials and Methods: A literature search was conducted for original, English‐language case reports, case series, original studies and/or meta‐analyses published between 1982‐2021 on isotretinoin, related adverse effects, and laboratory assessment and treatment nuances during and after a course of isotretinoin. Results: Adverse events categories include mucocutaneous (e.g., xerosis, cheilitis, epistaxis), ocular (xerophthalmia, nyctalopia, blepharitis, conjunctivitis), non‐specific gastrointestinal, musculoskeletal (myalgia, pre‐mature epiphyseal plate closure, DISH), neurologic (idiopathic intracranial hypertension, hearing loss, tinnitus). Most adverse events are mild, self‐limiting, and/or resolve with drug discontinuation. Teratogenicity is of utmost concern especially given the risk of patient nonadherence to iPLEDGE precautions. Laboratory testing at baseline and after month 2 of therapy or upon reaching maximum daily dose may be sufficient. Utilizing creatine kinase and gamma‐glutamyl transferase in lieu of aspartate aminotransferase and alanine aminotransferase may better assess hepatic function during treatment. Improved formulations of isotretinoin may improve absorption and decrease reliance on patient adherence to a high‐fat diet. Dermabrasion and fully ablative laser procedures should be avoided in the immediate post‐isotretinoin period. Discussion: Although adverse events associated with isotretinoin therapy are common, a majority of side effects are limited, self‐resolving (with completion of treatment course) without long‐term implications, and/or easily managed. Unfortunately, the advent of the internet and social media has given a platform to misleading law‐firm claims and medical pseudoscience inaccuracies that may frighten patients in need of treatment, ultimately delaying or even preventing therapy. Conclusion: It is important that physicians are knowledgeable about the nuances of isotretinoin therapy, including efficacy, real potential adverse events, and appropriate laboratory monitoring. By honing this expertise, physicians may confidently counsel and guide patients through a course of isotretinoin to achieve a more permanent solution for their acne and improve their quality of life.